Function discovery of a non-ribosomal peptide synthetase-like encoding gene in the nematode-trapping fungus Arthrobotrys oligospora - Gu, Tiantian; Lu, Hengqian; Liu, Huiwen; Zhang, Guanghui; Wang, Yongzhong (Frontiers in Microbiology, 2023)
In this study, the function of a non-ribosomal peptide synthetase-like(NRPS-like) encoding gene AOL_s00188g306 (g306) was investigated to reveal the association between NRPS and nematocidal activity in the nematode-trapping fungus Arthrobotrys oligospora. Sequence analysis indicated that the encoded product of g306 is an adenylation domain of non-ribosomal peptide synthetases and extended short-chain dehydrogenase/reductase domain-containing proteins, and displays a wide substrate spectrum. The Δg306 mutants were more sensitive to chemical stressors than the wild type. Disruption of g306 impeded the nematocidal efficiency of A. oligospora. Metabolomics analysis showed that secondary metabolite biosynthesis and lipid metabolism were altered in the mutants. The phenotypic changes in the mutants can be attributed to the down-regulation of various metabolites, including fatty acyls, prenol lipids, steroids and steroid derivative, and amino acid derivatives, identified in the present study. This study investigated the association between the non-ribosomal polypeptide-encoding gene g306 and nematicidal activity in A. oligospora, providing a reference for resolving the predation mechanism of nematode-trapping fungus.